A deep dive into cybersecurity solutions for AI-driven IoT-enabled smart cities in advanced communication networks - Ali, Jehad; Kumar Singh, Sushil; Jiang, Weiwei; Alenezi, Abdulmajeed M.; Islam, Muhammad; Ibrahim Daradkeh, Yousef; Mehmood, Asif (Computer Communications, 2025)
The integration of the Internet of Things (IoT) and artificial intelligence (AI) in urban infrastructure, powered by advanced information communication technologies (ICT), has paved the way for smart cities. While these technologies promise enhanced quality of life, economic growth, and improved public services, they also introduce significant cybersecurity challenges. This article comprehensively examines the complex factors in securing AI-driven IoT-enabled smart cities within the framework of future communication networks. Our research addresses critical questions about the evolving threat, multi-layered security approaches, the role of AI in enhancing cybersecurity, and necessary policy frameworks. We conduct an in-depth analysis of cybersecurity solutions across service, application, network, and physical layers, evaluating their effectiveness and integration potential with existing systems. The study offers a detailed examination of AI-driven security approaches, particularly ML and DL techniques, assessing their applicability and limitations in smart city environments. We incorporate real-world case studies to illustrate successful strategies and show areas requiring further research, especially considering emerging communication technologies. Our findings contribute to the field by providing a multi-layered classification of cybersecurity solutions, assessing AI-driven security approaches, and exploring future research directions. Additionally, we investigate the essential role played by policy and regulatory frameworks in safeguarding smart city security. Based on our analysis, we offer recommendations for technical implementations and policy development, aiming to create a holistic approach that balances technological advancements with robust security measures. This study also provides valuable insights for scholars, professionals, and policymakers, offering a comprehensive perspective on the cybersecurity challenges and solutions for AI-driven IoT-enabled smart cities in advanced communication networks.
Keywords: Communications networks; Communications security; Cyber security; Cybersecurity solution; Deep dives; Multi-layered; Network intelligence; Policy framework; Security approach; Smart city infrastructure; Artificial intelligence; Communication security; Cybersecurity solutions; Data privacy; Internet of Things; Network intelligence; Smart city infrastructure